The dynamics of Pandanus illustrations from a historical perspective - Sihotang, Vera Budi Lestari (REINWARDTIA, 2013)
Pandanaceae is placed in the superorder Pandaniflorae and the order Pandanales, indicating its uniqueness when compared with the other seed plants. Pandanaceae contains three genera, Pandanus, Sararanga and Freycinetia. Limited collections seem to be one reason why botanical illustrations are made, so that people can enjoy their "collections" from a picture painted on canvas. Botanical illustration is one type of record that can also give evidence about whether the plant exists. In addition, botanical illustration can give information about the growth of the plant, and historical evidence can be traced. There is no doubt that Pandanus has also been well illustrated. Later, further developments in Pandanus research obviously influenced the illustrations of Pandanus.